KAJIAN EKONOMIS PERBANDINGAN PEMBESARAN IKAN LELE SANGKURIANG (Clarias gariepenus) MENGGUNAKAN METODE SISTEM BIOFLOK DAN SISTEM KONVENSIONAL - Naharuddin Sri; Yusuf Kamlasi; Fajar Panuntun (Partner, 2022)
To increase catfish productivity, the Directorate General of Aquaculture continues to innovate and develop technology that results in a more efficient catfish enlargement system. The purpose of this study is to find out the most efficient and economically feasible sangkuriang catfish enlargement system between biofloc and conventional systems. From the results of water quality measurements of temperatures of 25-27oC, pH 7, DO 1.2 – 2.2, FCR 0.9 and 1.1 are still in the good range. From the financial analysis of the biofloc system the value of RC-Ratio: 1.1 while the conventional system RC Ratio: 1.03. The harvest life of the biofloc system is 80 days and the conventional system is 100 days. Based on the results of the analysis, it can be concluded that the enlargement of sangkuriang catfish using a biofloc system is more economical in terms of cost and time.  Keywords: catfish, biofloc, conventional, enlargement